Development of a small animal model for deer tick virus pathogenesis mimicking human clinical outcome - Hermance, Meghan E.; Hart, Charles E.; Esterly, Allen T.; Reynolds, Erin S.; Bhaskar, Jahnavi R.; Thangamani, Saravanan (PLOS Neglected Tropical Diseases, 2020)
Author summary Powassan virus (POWV) is a tick-borne flavivirus that can result in a fatal encephalitic disease in humans. Although POWV is closely related to deer tick virus (DTV), each virus is maintained in nature by unique transmission cycles. Because POWV and DTV are serologically indistinguishable and must be differentiated by genetic sequence analysis, an unknown portion of previously reported POWV cases may have actually been DTV cases. Overall, the scientific literature is sparse when it comes to describing confirmed DTV cases or the neurovirulence and clinical outcome for DTV-infected mice. Our study is the first to comprehensively characterize the survival rates, timeline of clinical disease, and tissue distribution of virus for mice infected with a range of DTV doses. Signs of disease in the DTV-infected mice mimicked the course of human clinical disease where neurological manifestations were preceded by a generalized febrile illness. Sequentially increasing doses of DTV did not elicit increased mortality rates or organ viral loads, which suggests that in this mouse model, virus infection and replication in tissues is independent of the infection dose. Our findings support the use of this mouse model in future DTV pathogenesis studies.